Relations of internalized stigma with temperament and character in patients with schizophrenia - Aukst-Margetić, Branka (Array, 2010)
Objective: The aim of the study was to assess the associations between self-stigma and temperament and character dimensions. Methods: One hundred twenty outpatients with diagnosis of schizophrenia, established with Mini International Neuropsychiatric Interview were consecutively included in the study. Self-stigma was assessed with Internalized Stigma of Mental Illness (ISMI), personality dimensions with Temperament and Character Inventory, and psychopathology with Positive and Negative Symptom Scale. Results: The results showed that higher level of harm avoidance, lower self-directedness, and persistence correlated with ISMI and all its subscales. Self-transcendence correlated with ISMI subscales alienation, discrimination, and stigma resistance. Regression analyses controlling for psychopathology, age, length of illness, and number of hospitalizations revealed that higher level of harm avoidance and low self-directedness predicted internalized stigma. Conclusion: The finding suggests that the experience of self-stigma is related to personality dimensions. Interpretations of these findings include the possibility that, irrespective of patients' psychopathology or functional characteristics, experience of self-stigma and its consequences might depend on personality dimensions. Further studies are needed